Experimental and numerical investigations of the effectiveness of engineered cementitious composites and stainless steel plates in shear strengthening of reinforced concrete beams. (18th August 2022) - Hamoda, Ahmed; Ahmed, Mizan; Sennah, Khaled
Abstract: This paper investigates the shear strengthening of reinforced concrete (RC) beams incorporating engineered cementitious composite (ECC) and stainless steel plates (SSPs). The use of ECC, characterized by strain‐hardening in conjunction with SSPs, was investigated in this study to improve the shear performance of RC beams. Total 10 RC beams were tested under static loading up to failure to investigate a few key parameters, namely: material of strengthening (ECC and SSPs), the thickness of ECC, and shape and configuration of SSPs. Experimental findings showed that the proposed strengthening methods can significantly improve the failure pattern and increase the ultimate shear capacity of the studied RC beams by 36%–97% compared to the unstrengthened beam. Experimental results were compared against the predicted ultimate shear strength of RC beams using design equations specified by various design codes. Nonlinear three‐dimensional finite element modeling was developed for beams strengthened with ECC layer and validated against the test results and found to be accurate. Based on the experimental and numerical results, new shear capacity formulae were proposed considering the ratio of ECC‐to‐concrete beam cross‐section ( ρ ECC ) and then verified against the numerical predictions.